Platycranus (Genistopapsus) boreae sp. nov. from Slovenia (Hemiptera: Heteroptera: Miridae: Orthotylinae) - Gogala, Andrej (Acta entomologica slovenica (Ljubljana), 2002)
Platycranus boreae sp. nov. is described. It was found at the top of Mt. Lipnik in Čičarija, northern Istria, Slovenia, about 800 m above sea level. Its foodplant is Genista sericea, which is endemic to the western part of the Balkans. With the exception of P. (G.) wagneri, the new species is the smallest member of the subgenus Genistocapsus. Very short antennae distinguish it from other completely green species of the subgenus Genistocapsus, they are similar only in P. jurineae, P. remanei, P. minutus and P. orientalis. It can be distinguished from them by the proportions, measures of some body parts, and the shape of the parameres. The most closely related species seems to be P. jurineae from Ukraine.
Keywords: Hemiptera; Slovenia; Slovenija; stenice; zoogeografija; zoologija; zoology